Standards in the classroom : an implementation guide for teachers of science and mathematics - Audet, Richard A.; Jordan, Linda K. (Thousand Oaks, CA : Corwin Press, 2003)
This guide is an absolute must for teachers, administrators, and professors to provide the support needed for effective implementation of standards in the classroom.
1. Engagement: thinking about standards and instruction -- 2. Exploration: discovering national standards resources -- 3. Explanation I: researching national standards to clarify learning goals -- 4. Explanation II: assessment in a standards-based system -- 5. Extension I: developing standards-based curriculum materials -- 6. Extension II: analyzing and evaluating curriculum materials -- 7. Extension III: curriculum mapping -- 8. Evaluation: discoveries about standards-based teaching and learning -- 9. Endurance: sustaining change -- References and further readings -- Resource: professional development designs.
Includes bibliographical references and index.
Keywords: MATHEMATICS -- STUDY AND TEACHING -- STANDARDS; SCIENCE -- STUDY AND TEACHING -- STANDARDS